(untitled) (The Lumbini Journal of Business and Economics, 2025)
Purpose: Every truck crossing the Birgunj-Raxaul checkpoint carries more than goods. It carries the weight of India–Nepal interdependence. Despite long-standing treaties, the corridor still mirrors South Asia’s paradox: deep proximity, shallow coordination. This study examines how bilateral trade has evolved since 2010, what infrastructural and institutional bottlenecks persist, and how digital initiatives are reshaping this interdependence. Methods: Using a mixed-methods approach, the study combines quantitative analysis of official trade data (DGFT, NRB) with twenty semi-structured interviews involving traders, customs officials, and logistics experts to link numbers with lived realities. Results: Trade rose from USD 4.2 billion in 2010 to about USD 11 billion in 2023, yet remains uneven. Digital reforms under BBIN and customs automation improved processing times but failed to eliminate manual checks, power outages, and fragmented coordination. Conclusion: Transforming geographic closeness into genuine connectivity demands synchronized digital platforms, harmonized procedures, and trust-based institutional cooperation – turning border crossings from choke points into channels of shared prosperity.